Scaling Up Culinary MSMEs for Local Economic Growth: A Study of Pontianak’s Transition from Micro to Small/Medium Enterprises - Setiawan, Aris; Maulana, Uray Andrey Indra; Mayasafitri, Rina (Yayasan Riset dan Pengembangan Intelektual, 2025)
The transition of Micro, Small, and Medium Enterprises (MSMEs) to a sustainable economy in the 4.0 era is crucial for economic development and environmental sustainability in many countries. MSMEs face various challenges in continuing to grow and develop. Adopting information technology is important to continue supporting MSMEs in growing optimally. The development of MSMEs must be supported by easy access to Capital and favour MSMEs. This study aims to test and analyze the effect of information technology, access to Capital, and government policies on the transition of culinary MSMEs from Micro to small and medium in Pontianak City. This research used a quantitative approach with multiple regression analysis tools and the SPSS 25 test tool. The data collection technique was carried out by interviewing and distributing questionnaires. The number of samples in this study was 279 respondents. The results of this study show that information technology, access to Capital, and government regulations have a positive and significant effect on the transition of Micro to small and medium enterprises. Research should involve other factors, such as human resource training for MSME owners, so that they can take advantage of the growing technology.